Transient Coatings from Nanoparticles Achieving Broad-Spectrum and High Antimicrobial Performance - Rachel Zaia; Giovanna M. Quinto; Livia C. S. Camargo; Rodrigo T. Ribeiro; Ana M. Carmona-Ribeiro (MDPI AG, 2023)
Cationic and hydrophilic coatings based on casting and drying water dispersions of two different nanoparticles (NPs) onto glass are here described and evaluated for antimicrobial activity. Discoid cationic bilayer fragments (BF) surrounded by carboxy-methylcellulose (CMC) and poly (diallyl dimethyl ammonium) chloride (PDDA) NPs and spherical gramicidin D (Gr) NPs dispersed in water solution were cast onto glass coverslips and dried, forming a coating quantitatively evaluated against Pseudomonas aeruginosa, Staphylococcus aureus and Candida albicans. From plating and colony forming units (CFU) counting, all strains interacting for 1 h with the coatings lost viability from 105 to 106, to zero CFU, at two sets of Gr and PDDA doses: 4.6 and 25 μg, respectively, or, 0.94 and 5 μg, respectively. Combinations produced broad spectrum, antimicrobial coatings; PDDA electrostatically attached to the microbes damaging cell walls, allowing Gr NPs interaction with the cell membrane. This concerted action promoted optimal activity at low Gr and PDDA doses. Further washing and drying of the deposited dried coatings showed that they were washed out so that antimicrobial activity was no longer present on the glass surface. Significant applications in biomedical materials can be foreseen for these transient coatings.